Time-of-flight spectra for mapping of charge density of ions produced by laser. (March 2014) - Krása, J.; Parys, P.; Velardi, L.; Velyhan, A.; Ryć, L.; Delle Side, D.; Nassisi, V.
Abstract: A space-resolved charge density of ions is derived from a time-resolved current of ions emitted from laser-produced plasma and expanded into the vacuum along collision-free and field-free paths. This derivation is based on a similarity relationship for ion currents with "frozen" charges observed at different distances from the target. This relationship makes it possible to determine a map of ion charge density at selected times after the laser plasma interaction from signals of time-of-flight detectors positioned at a certain distance from the target around a target-surface normal. In this work, we present maps of the charge density of ions emitted from Cu and polyethylene plasmas. The mapping demonstrates that bursts of ions are emitted at various ejection angles ϕ n with respect to the target-surface normal. There are two basic directions ϕ 1 and ϕ2, one belonging to the fastest ions, i.e., protons and carbon ions, and the other one to the slowest ions being a part of each plasma plume.